A new species of Catocala Schrank, 1802 (Lepidoptera: Noctuidae) from Primorsky Krai, Russia - Kons Jr., Hugo L.; Borth, Robert J.; Saldaitis, Aidas (Zootaxa, 2016)
Here we describe Catocala didenko sp. n. as new for the noctuid genus Catocala Shrank, differing from Catocala duplicata Butler, 1885 and Catocala gansan Ishizuka & Wang, 2013 on wing pattern, male genitalia, and COI 5’ mitochondrial DNA. These three species, along with Catocala dissimilis Bremer, 1861, comprise a small and distinctive species group within the genus. Exemplary uncommon morphological characters for this group include: extensive area of ventral side of claspers unsclerotized (Fig. 17); claspers with a subapical ventral bulging projection (Fig. 17); sclerotized apex of claspers greatly expanded laterally (Fig. 17); diaphragma posterior to anellus lightly pigmented (Fig. 22); distinctive anellus shape (Fig. 22); uncus setae longest and densest at base (Fig. 21); and approximately 17-20 coils on the receptacle duct (Fig. 56).